Diseases of common carp and their control measures - Rahman, Mohammad Mustafizur; Mansor, Nur Nazifah; Balcombe, Stephen Richard (NOVA Science Publishers, 2018)
Common carp (Cyprinus carpio L.) contribute significantly to global freshwater fish production but it may also play a significant role in the expansion of various parasitic fish diseases around the globe as many parasites were dispersed locally and internationally due to common carp trade. The production of common carp in natural habitats and in aquaculture farms often become threatened due to various factors including disease outbreaks. Disease increases the management costs as well as decreasing fish production. To prevent and control various diseases, it is important to understand the mechanism of disease outbreak, which generally involves a complex interaction among fish, pathogens and the environment. High stocking density, poor management practices and various environmental problems result in exposure of fishes to stress that often leads to disease. The disease can also be initiated by various biological agents, which can be prevented and controlled by effective management practises. Due to the preference of soft vegetated sediments as habitat, common carp is also susceptible to many pathogens (e.g., viruses, bacteria, fungi, parasites, etc.), which cause various diseases. A severe pathogenic infection may cause high mortality of fish. This paper reviews various diseases of common carp and their control measures.